2019
DOI: 10.1039/c8ay02287a
|View full text |Cite
|
Sign up to set email alerts
|

Chiral analysis of β-methylamino alanine (BMAA) enantiomers after (+)-1-(9-fluorenyl)-ethyl chloroformate (FLEC) derivatization and LC-MS/MS

Abstract: A developed method for chiral analysis of neurotoxin β-methylamino alanine (BMAA) allowed detection of d-BMAA in cycad seed samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Analytical methods and laboratory equipment have progressed from fluorescence to mass spectrometric detection, with or without chemical derivatization to provide accurate and specific detection of these molecules [85]. Although such methods are useful for isolating and quantifying BMAA and its isomers, so far, methods to understand the enantiomers of such compounds are limited [86][87][88]. BMAA was originally isolated from an ethanolic extract of cycad seeds, and an optical analysis of the compound determined the presence of the L-enantiomer [89,90].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analytical methods and laboratory equipment have progressed from fluorescence to mass spectrometric detection, with or without chemical derivatization to provide accurate and specific detection of these molecules [85]. Although such methods are useful for isolating and quantifying BMAA and its isomers, so far, methods to understand the enantiomers of such compounds are limited [86][87][88]. BMAA was originally isolated from an ethanolic extract of cycad seeds, and an optical analysis of the compound determined the presence of the L-enantiomer [89,90].…”
Section: Introductionmentioning
confidence: 99%
“…BMAA has been analytically detected in cyanobacteria [87,100] and is considered to also be produced by diatoms and possibly dinoflagellates [101][102][103][104][105][106], although little research has been performed on the enantiomers that are present in these organisms. Previous methods have separated synthetic L-and D-BMAA standards using derivatized [86,88] and underivatized [87] methods. The presence of BMAA enantiomers has been investigated in cycads [87,88], cyanobacteria and in mammalian liver, blood and CNS after dosing with synthetic L-BMAA [87].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurotoxins cause an amyotrophic lateral sclerosis/parkinsonism-dementia complex (ALS-PDC) (Brownson et al, 2002; Meneely et al, 2016). ALS-PDC is a progressive neurodegenerative disease that infected high number of Chamorro people in Guam (Metcalf et al, 2017; Zurita et al, 2019). The disease was believed to be transmitted by flying foxes that consumed cycad seeds.…”
Section: Introductionmentioning
confidence: 99%
“…This neurotoxin was claimed to be β-methylamino-L-alanine (BMAA), a non-proteinogenic amino acid produced by cyanobacteria. Even though some studies have showed that cycad host plants contain BMAA (Vega and Bell, 1967; Polsky et al, 1972; Brownson et al, 2002; Banack and Cox, 2003; Cox et al, 2003), an accurate detection method of BMAA is still being perfected until the present (Metcalf et al, 2017; Zurita et al, 2019) due to various structural isomers (Rosén and Hellenäs, 2008; Banack et al, 2010; Jiang et al, 2012) making it difficult to correctly identify the compound as BMAA. And thus, all previous claims that BMAA was detected still needed further validation.…”
Section: Introductionmentioning
confidence: 99%